Genetic Alterations in Gastric Cancer Associated with Helicobacter pylori Infection - Rivas-Ortiz, Claudia I.; Lopez-Vidal, Yolanda; Arredondo-Hernandez, Luis Jose Rene; Castillo-Rojas, Gonzalo (Frontiers in Medicine, 2017)
Gastric cancer is a world health problem, and depicts the fourth leading mortality cause from malignancy in Mexico. Causation of gastric cancer is not only due to the combined effects of environmental factors and genetic variants. Recent molecular studies have transgressed a number of genes involved in gastric carcinogenesis. The aim of this review is to understand the recent basics of gene expression in the development of the process of gastric carcinogenesis. Genetic variants, polymorphisms, DNA methylation, and genes involved in mediating inflammation, have been associated with the development of gastric carcinogenesis. Recently, these genes (IL-10, Il-17, MUC1, β-catenin, CDX1, SMAD4, SERPINE1, HIF-1α, GSK3β, CDH17, MMP7, RUNX3, RASSF1A, TFF1, HAI-2 and COX-2) have been studied in association with oncogenic activation or inactivation of tumor suppressor genes. All these mechanisms have been investigated to elucidate the process of gastric carcinogenesis, as well as their potential use as biomarkers and/or molecular targets to treatment of disease.